2021
DOI: 10.3390/healthcare9111563
|View full text |Cite
|
Sign up to set email alerts
|

Micropulse Transscleral Cyclophotocoagulation as Primary Surgical Treatment for Primary Open Angle Glaucoma in Taiwan during the COVID-19 Pandemic

Abstract: Glaucoma is the leading cause of irreversible blindness worldwide, with primary open angle glaucoma (POAG) accounting for the greatest number of total glaucoma cases. This study aimed to evaluate the efficacy and safety of micropulse transscleral cyclophotocoagulation (MP-TSCPC) as a primary procedure in POAG during the COVID-19 pandemic. We retrospectively analyzed 60 eyes of 52 patients, who were diagnosed with mild-to-end-stage POAG without previous glaucoma surgery and received MP-TSCPC between 1 January 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 61 publications
(80 reference statements)
0
13
1
Order By: Relevance
“…19 Glaucoma remains the leading cause of irreversible blindness worldwide, with primary open angle glaucoma accounting for the greatest number of total glaucoma cases. 20 The principal findings of this study was that the overall prevalence of HBV, HCV and HIV was 2.41%, 1.45% and 3.22 respectively. Additionally, the prevalence of HBV was significantly higher in males compared to female counterparts.…”
Section: Discussionmentioning
confidence: 67%
“…19 Glaucoma remains the leading cause of irreversible blindness worldwide, with primary open angle glaucoma accounting for the greatest number of total glaucoma cases. 20 The principal findings of this study was that the overall prevalence of HBV, HCV and HIV was 2.41%, 1.45% and 3.22 respectively. Additionally, the prevalence of HBV was significantly higher in males compared to female counterparts.…”
Section: Discussionmentioning
confidence: 67%
“…MPTLT-related pain has been reported in the literature. Table 4 summarizes the study characteristics and the pain outcomes from five previous studies [ 3 , 4 , 12 , 13 , 14 ]. Tan et al and Chang et al demonstrated considerably lower prevalence of pain than Yelenskiy et al and our study, whereas Preda et al and Popa et al reported mean visual analog scale values that were comparable to our mean NRS value.…”
Section: Discussionmentioning
confidence: 99%
“…Despite receiving local anesthesia, some patients who undergo MPTLT report pain that might affect their quality of life and ability to perform activities of daily living. Few studies have evaluated pain due to MPTLT, and most have focused only on pain during the procedure [ 3 , 4 , 12 , 13 , 14 ]. This study aimed to assess the pain during the procedure as well as the overnight pain after MPTLT under retrobulbar anesthesia and explore the factors associated with the two types of pain.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 It has recently gained more popularity, even for milder glaucoma with good visual potential. 3 , 4 It is a short, effective, and easy-to-apply procedure; however, there are several possible complications, including pupillary distortion, disturbed accommodation, conjunctival burn, uveitis, hyphema, cystoid macular edema, chronic hypotony, retinal detachment, and phthisis bulbi. 5 , 6 , 7 Scleral perforation is an uncommon complication of transscleral CPC, with few cases reported in the literature.…”
Section: Introductionmentioning
confidence: 99%